Diverse reactivity of glycals with arylamines and sulfonamides : synthesis of 4-aminocyclopentenones, cyclopentanone fused indolines and sialic acid - Wang, Siming (2013)
The diverse class of N-containing compounds, which comprises various biologically important natural and unnatural substances with complex molecular architecture, has challenged synthetic chemists to devise imaginative strategies towards their construction. This thesis discusses salient synthetic methodologies to access N-containing compounds including 4-aminocyclopentenones, cyclopentanone-fused indolines and sialic acid from readily available glycals.By judicious choice of the reaction solvent, an array of 4-aminocyclopentenones or cyclopentanone fused indolines was synthesized from common glycals and secondary arylamines. This novel methodology involves an interrupted Nazarov process in which the cyclopentenyl cation intermediate is captured by water or aryl moieties. In addition, we have developed a methodology that allows facile synthesis of common and uncommon sialic acids. This methodology employs a tandem Rh-catalyzed nitrene insertion and Barbier allylation as the key step.